PEDAGOGICAL OPTIMIST OR PEDAGOGICAL PESSIMIST: WHO AM I? - A. S. Robotova (Высшее образование в России)
The author regards the following text not as an article, but as reflections caused by A.A. Polonnikov's article "Modern educational situation: approaches to the description and discursive responsibility." It raises issues that are extremely important for the development of pedagogy, encourages critical analysis of a system of pedagogical language. But what is the most important - that it speaks to those who are closely involved in educational science and puts a question of discursive responsibility. Disregard of this question becomes a hindrance in the development of pedagogical knowledge, in understanding of the educational situation, in finding an answer to the question: who I am as an author of a pedagogical text.